The first complete mitogenome of the South China deep‐sea giant isopod Bathynomus sp. (Crustacea: Isopoda: Cirolanidae) allows insights into the early mitogenomic evolution of isopods. Issue 6 (16th February 2017) - Shen, Yanjun; Kou, Qi; Zhong, Zaixuan; Li, Xinzheng; He, Lisheng; He, Shunping; Gan, Xiaoni
Abstract: In this study, the complete mitochondrial (mt) genome sequence of the South China deep‐sea giant isopod Bathynomus sp. was determined, and this study is the first to explore in detail the mt genome of a deep‐sea member of the order Isopoda. This species belongs to the genus Bathynomus, the members of which are saprophagous residents of the deep‐sea benthic environment; based on their large size, Bathynomus is included in the "supergiant group" of isopods. The mt genome of Bathynomus sp. is 14, 965 bp in length and consists of 13 protein‐coding genes, two ribosomal RNA genes, only 18 transfer RNA genes, and a noncoding control region 362 bp in length, which is the smallest control region discovered in Isopoda to date. Although the overall genome organization is typical for metazoans, the mt genome of Bathynomus sp. shows a number of derived characters, such as an inversion of 10 genes when compared to the pancrustacean ground pattern. Rearrangements in some genes (e.g., cob, trnT, nad5, and trnF ) are shared by nearly all isopod mt genomes analyzed thus far, and when compared to the putative isopod ground pattern, five rearrangements were found in Bathynomus sp. Two tRNAs exhibit modified secondary structures: The TΨC arm is absent from trnQ, and trnC lacks the DHU. Within the class Malacostraca, trnC arm loss is only found in other isopods. Phylogenetic analysis revealed that Bathynomus sp. (Cymothoida) and Sphaeroma serratum (Sphaeromatidea) form a single clade, although it is unclear whether Cymothoida is monophyletic or paraphyletic. Moreover, the evolutionary rate of Bathynomus sp. (dN/dS [nonsynonymous mutational rate/synonymous mutational rate] = 0.0705) is the slowest measured to date among Cymothoida, which may be associated with its relatively constant deep‐sea environment. Overall, our results may provide useful information for understanding the evolution of deep‐sea Isopoda species. Abstract : This study is the first to explore in detail the mitochondrial (mt) genome of a deep‐sea member of the order Isopoda. The mitogenome of Bathynomus sp. is 14, 965 bp in length but only 18 transfer RNA genes and a non‐coding control region 362 bp in length, which is the smallest control region discovered in Isopoda to date. The mt genome of Bathynomus sp. shows a number of derived characters, such as an inversion of 10 genes when compared to the pancrustacean ground pattern. The evolutionary rate of Bathynomus sp. is the slowest measured to date among Cymothoida, which may be associated with its relatively constant deep‐sea environment.